Mapping postcommunist cultures : Russia and Ukraine in the context of globalization - Chernetsky, Vitaly (McGill-Queen's University Press, 2007)
Drawing on the discourses of postmodernism, postcolonialism, and globalization, Vitaly Chernetsky maps out the new cultural developments in literature, architecture, painting, film, and performance art emerging in Russia and Ukraine, the two largest successor states to the Soviet Union, situating these phenomena in a greater global context.